Maghrib Community’s Qur’anic Recitation Movement: an Effort to Maintain The Tradition of Reciting The Quran Among Indonesian Muslim - Serli Roisca (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The crucial circumstances of Moslems toward Al-Quran and the termination of governmentnoble program underlined this scientific paper. The underlying problems can be formulized as follow: how do we conceptualize something suitable for, and even can unite Muslim communities that are separated from each other in terms of time and place through Maghrib Reciting Quran Community Movement. This paper also discusses related strategy needed to revive and maintain this noble program again in order to maintain the tradition of reciting the Quran in Indonesian Muslim community. Key words: Indonesian muslim, Maghrib community, Quranic recitation tradition